Penerapan Keadilan Restoratif oleh Bhabinkamtibmas di Kepolisian Sektor Soreang - Rachman, Fitriana Sidikah; Srijadi, Yana Kusnadi; Zairusi (Jurnal Pengabdian Tri Bhakti, 2023)
Since the issuance of the Regulation of the Republic of Indonesia National Police No. 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice, the National Police has increasingly emphasized its policy to implement Restorative Justice. Restorative Justice is a step to resolve problems outside of retributive law enforcement mechanisms. In restorative justice, the principle of ultimum remedium applies, where criminalization is the last alternative for punishing a crime. Therefore, there needs to be an in-depth study for Bhabinkamtibmas members regarding the implementation of Restorative Justice. The goal is for Bhabinkamtibmas members to be more professional in carrying out their duties as fosterers of public security and order, especially related to the implementation of Restorative Justice in resolving criminal cases in their environment. The method used is through interactive discussions on various problems encountered in the field and the delivery of learning materials by Abdimas. Based on the results of the implementation during PkM, there was an increase in knowledge among Bhabinkamtibmas members, especially in-depth study of the implementation of Restorative Justice, communication and conflict management. It is hoped that this can improve the professionalism of Bhabinkamtibmas members in implementing Restorative Justice in accordance with their field of duty.